To solve the equation, let's simplify and combine like terms first:
Starting with the left side of the equation, simplify the expression "-x + 3 + 6x":
(-x) + 6x + 3
Combine the "x" terms:
5x + 3
Now, let's do the same with the right side of the equation, simplify the expression "2 + 5x + 3":
2 + 5x + 3
Combine the "2" and "3":
5 + 5x
So the given equation becomes:
5x + 3 = 5 + 5x
Now, let's solve for "x":
Subtract 5x from both sides:
5x - 5x + 3 = 5 - 5x + 5x
Simplify:
3 = 5
Since the equation simplifies "3 = 5", which is not a true statement, there is no solution to this equation.
Solve:
`-x+3+6x=2+5x+3`
3 answers
no solution or identity ?
Apologies for the confusion. You are correct, the equation simplifies to an identity rather than a numerical contradiction.
Starting with the equation:
5x + 3 = 5 + 5x
Let's subtract 5x from both sides:
5x - 5x + 3 = 5 - 5x +5x
3 = 5
Since the equation simplifies to "3 = 5", which is not true, there is no solution to this equation. Therefore, the correct answer is that there is no solution.
Starting with the equation:
5x + 3 = 5 + 5x
Let's subtract 5x from both sides:
5x - 5x + 3 = 5 - 5x +5x
3 = 5
Since the equation simplifies to "3 = 5", which is not true, there is no solution to this equation. Therefore, the correct answer is that there is no solution.